A robust anionic pillared-layer framework with triphenylamine-based linkers: ion exchange and counterion-dependent sorption properties. Issue 20 (19th April 2017) - Akintola, Oluseun; Ziegenbalg, Sven; Buchholz, Axel; Görls, Helmar; Plass, Winfried
Abstract : Tricarboxyltriphenylamine and terephthalic acid act as linkers in a pillared-layer anionic cobalt(ii ) framework. The counterions can be exchanged while keeping the framework intact, leading to improved sorption properties for small lithium ions. Abstract : A new anionic pillared-layer cobalt(ii ) metal–organic framework combining 4, 4′, 4′′-nitrilotribenzoic acid (H3 ntb) as a linker and terephthalic acid (H2 bdc) as a pillar-ligand with the formula ((CH3 )2 NH2 )2 [Co3 (ntb)2 (bdc)] n (JUMP-1, JUMP = Jena University Magnetic Polymer) has been solvothermally synthesized and characterized. The crystal structure of JUMP-1 was determined to belong to the orthorhombic space group Cmca . It displays a three-dimensional (3D) framework for which the topological analysis revealed a 3, 8-connected net with a tfz-d topology. The 3-connected organic node is linked to an 8-connected secondary building unit composed of a linear trinuclear cobalt(ii ) cluster with a mixed arrangement of coordination geometries ( T d – O h – T d ) leading to two-dimensional layers which are further linked by terephthalic acid to give the pillared-layer arrangement. The magnetic properties are characterized by an antiferromagnetic coupling between a central octahedrally coordinated cobalt(ii ) ion and two outer tetrahedral cobalt(ii ) centers, whereas only a very weak inter-cluster coupling is observed. Moreover, a moderate zero-field splitting is detected for the tetrahedral cobalt(ii ) ions. The organic counterions could successfully be exchanged by lithium ions under retention of the anionic 3D network leading to JUMP-1(Li). For both compounds JUMP-1 and JUMP-1(Li), N2 and CO2 adsorption isotherms were measured. The pore distribution analyses revealed improved microporosity for the lithium exchanged MOF.